THE INFLUENCE OF THE THERAPEUTIC ALLIANCE ON ADHERENCE TO PSYCHOLOGICAL TREATMENT: A LITERATURE REVIEW - da Mata, Andréia Oliveira; Cecchin, Hareli Fernanda Garcia (Seven Editora, 2026)
Adherence to psychological treatment remains a significant challenge in clinical practice, particularly given the rates of premature dropout observed across different therapeutic contexts. In this scenario, the therapeutic bond has been consistently identified as a key factor associated with patient engagement and continuity in psychotherapy. This study aimed to understand, based on scientific literature, how the therapeutic bond influences adherence to psychological treatment. A narrative literature review was conducted using the Scielo and Google Scholar databases, including articles published between 2015 and 2025. Eligible studies were full-text, freely available articles written in Portuguese or English that addressed the therapeutic bond within the context of psychotherapy. After applying the inclusion and exclusion criteria, 14 articles were selected for analysis. The findings indicate convergence regarding the central role of the therapeutic bond in treatment adherence, highlighting elements such as empathy, trust, collaboration, and shared goal-setting as factors associated with patients’ permanence in the psychotherapeutic process. The studies also show that a fragile therapeutic alliance is related to treatment dropout, particularly in institutional settings, psychotherapy with children and adolescents, and online modalities. It is concluded that the therapeutic bond is an essential component of psychotherapy effectiveness, functioning as a protective factor against dropout and should be understood as a dynamic relational process, sensitive to clinical contexts and patients’ needs.